Digital Ilustration: Form Sketch to Screen in Design Skill Workshop 2025 - Vikky Aprelia Windani; Amirudin Khorul Huda; Suya Tri Atmja; Fiyas Mahaning Puri; Dewi Anisa Istiqomah (Cahaya Pengabdian, 2026)
Graphic design is a highly relevant skill for today's digital generation. Graphic design allows for visual communication, allowing for easier understanding of ideas, concepts, and messages. Mastery of graphic design is crucial for teachers in creating creative, interactive learning media, and enhancing student interest and motivation. For students with non-IT backgrounds, graphic design is not a compulsory subject, requiring them to learn independently. Based on these issues, this community service activity was implemented as a form of training and mentoring related to the use of graphic design using the popular and easy-to-use Canva application. This activity was aimed at students belonging to the English Language Education Program Student Association, Faculty of Tarbiyah, State Islamic University of Salatiga. The results of the questionnaire evaluation showed that the program was very effective and exceeded the threshold of success. The overall average was 4.39 out of 5, with all respondents scoring at least 4. Facilities emerged as a key strength, with an average of 4.40, which facilitated smooth practice. Participants' self-efficacy was high at 4.39, with the material presented and delivery solid at 4.38. Assignments were rated clear and realistic, with an average score of 4.38, although a small number of participants still hoped for a more refined work rhythm. Relevance and impact were rated at 4.37, while satisfaction reached 4.38. Overall, the learning experience was rated excellent, objectives were achieved, and the foundation for the program's sustainability is strong.